O sentido expresso por conjunções coordenativas no discurso sob a perspectiva da teoria da argumentação na língua - Aragão, Roberta Lara de Oliveira (2015)
The aim of this study is to explain the meaning created by the relationship that coordinating conjunctions establish between the clauses that they connect, according to the Theory of Argumentation within Language in its current phase, the Theory of Semantic Blocks developed by Oswald Ducrot, Jean-Claude Anscombre and Marion Carel. The objective is to explain these relationships through a semantic approach that takes into consideration aspects that compose the meaning of the conjunctions themselves, without necessarily being in accordance with grammatical terminology. Furthermore, the intent is to seek meaning starting from the premise that it is in their use that coordinating conjunctions actually assume their meaning, case by case.